ChemInform Abstract: Evaluation of 5‐cis‐Substituted Prolinamines as Ligands in Enantioselective, Copper‐Catalyzed Henry Reactions. Issue 40 (September 2016) - Kaldun, Johannes; Prause, Felix; Scharnagel, Dagmar; Freitag, Frederik; Breuning, Matthias
Abstract: The newly synthesized ligands prove useful in the scalable Henry reaction of aromatic, hetaromatic and aliphatic aldehydes.